QSAR AND DOCKING STUDY ON INDOLIZINES BY SIMILARITY CLUSTERING - SZEFLER, Beata; HARSA, Teodora E.; HARSA, Alexandra M. (Studia Universitatis Babeș-Bolyai Chemia, 2015)
A Quantitative Structure-Activity Relationship study, based on molecular descriptors calculated with correlation weights within the hypermolecule, that mimics the investigated correlational space, was performed on a set of 25indolizines (PubChem database). The best models describing IC50 of this set of indolizines were validated by the leave-one-out procedure, in the external test set and in a new version of prediction by using clusters of similar molecules. The best prediction was provided by the similarity cluster procedure.